New American Alliances in East Asia - The AUKUS Alliance as a Model - (Journal of the College of Basic Education, 2026)
The United States has been working to establish new alliances in East Asia since President Joe Biden entered the White House. This strategy has been adopted by Washington to confront adversaries and enhance security and stability in East Asia. This strategy is based on avoiding direct confrontation between the United States and its regional power rivals, particularly China, with its rapid rise and global ambitions. Washington seeks to contain China's influence, create a strategic balance, and enhance the United States' pivotal role in East Asia. East Asia is a cornerstone of the global balance of power, experiencing escalating tensions and highly sensitive economic and political conflicts.